Researcb on New Internet Quality of Service Guarantee Tecbnology - Fei Meng; Julong Lan; Yuxiang Hu (Dianxin kexue)
The scale of network traffic grows rapidly and the video trend of network traffic is becoming more and more serious, which make the traditional network architecture designed for data transmission can hardly satisfy current demands in quality of service（QoS）guarantee,flexibility,scalability,and other aspects.Industry and academia made a lot of new network architecture, aimed at enhancing the QoS capability at the architecture level. New internet QoS guarantee technology in both“incremental”and“clean slate”aspects was analyzed explicitly. In addition, wide-sense circuit and its deployment were introduced. Reconfigurable network architecture can adapt to future application development network and meet the compatible integration of evolution needs of existing network, with the characteristics of its adaptability to applications and functions scalability, providing a solution for the QoS guarantee of future network.